Structure-Function Implications of the Ability of Monoclonal Antibodies Against α-Galactosylceramide-CD1d Complex to Recognize β-Mannosylceramide Presentation by CD1d - Clark, Katharine; Yau, Jessica; Bloom, Anja; Wang, Jing; Venzon, David J.; Suzuki, Motoshi; Pasquet, Lise; Compton, Benjamin J.; Cardell, Susanna L.; Porcelli, Steven A.; Painter, Gavin F.; Zajonc, Dirk M.; et al. (Frontiers in Immunology, 2019)
iNKT cells are CD1d-restricted T cells recognizing lipid antigens. The prototypic iNKT cell-agonist a-galactosylceramide (a-GalCer) alongside compounds with similar structures induces robust proliferation and cytokine production of iNKT cells and protects against cancer in vivo. Monoclonal antibodies (mAbs) that detect CD1d-a-GalCer complexes have provided critical information for understanding of antigen presentation of iNKT cell agonists. Although most iNKT cell agonists with antitumor properties are a-linked glycosphingolipids that can be detected by anti-CD1d-a-GalCer mAbs, b-ManCer, a glycolipid with a b-linkage, induces strong antitumor immunity via mechanisms distinct from those of a-GalCer. In this study, we unexpectedly discovered that anti-CD1d-a-GalCer mAbs directly recognized b-ManCer-CD1d complexes and could inhibit b-ManCer stimulation of iNKT cells. The binding of anti-CD1d-a-GalCer mAb with b-ManCer-CD1d complexes was also confirmed by plasmon resonance and could not be explained by a-anomer contamination. The binding of anti-CD1d-a-GalCer mAb was also observed with CD1d loaded with another b-linked glycosylceramide, b-GalCer (C26:0). Detection with anti-CD1d-a-GalCer mAbs indicates that the interface of the b-ManCer-CD1d complex exposed to the iNKT cell TCR can assume a structure like that of a-GalCer-CD1d, despite its disparate carbohydrate structure. These results suggest that certain b-linked monoglycosylceramides can assume a structural display similar to that of a-GalCer-CD1d.